Perioperative management of patients with congenital or acquired disorders of the QT interval. (April 2018) - O'Hare, M.; Maldonado, Y.; Munro, J.; Ackerman, M.J.; Ramakrishna, H.; Sorajja, D.
Abstract: QT prolongation can be attributable to various causes that can be categorised as acquired or congenital. Arrhythmias related to QT prolongation can result in clinical presentations, such as syncope and sudden cardiac death. The perioperative period presents a number of issues that may affect a patient's risk of developing polymorphic ventricular tachycardia or torsades de pointes. Although most patients may have an unremarkable perioperative course, some may have complications; this review article aims to help clinicians avoid potential complications, and to help them address treatment for perioperative issues that may occur.